An unexpected father - Ferrarella, Marie (Fortunes of Texas., 2021)
"Reformed playboy Brady Fortune has suddenly become legal guardian to his best friend's little boys, and he is in over his head...until Harper Radcliffe comes to the rescue. His new nanny makes everything better, but her past makes her wary. Can Brady convince her they can somehow form a family? Their Fortune bunch won't feel complete without her!"--Back cover.